Research progress of EMOFs-based burning rate catalysts for solid propellants - Tan, Bojun; Yang, Xiong; Dou, Jinkang; Duan, Binghui; Lu, Xianming; Liu, Ning (Frontiers in Chemistry, 2022)
Energetic Metal Organic Frameworks (EMOFs) have been a hotspot of research on solid propellants in recent years. In this paper, research on the application of EMOFs-based burning rate catalysts in solid propellants was reviewed and the development trend of these catalysts was explored. The catalysts analyzed included monometallic organic frameworks-based energetic burning rate catalysts, bimetallic multifunctional energetic burning rate catalysts, carbon-supported EMOFs burning rate catalysts, and catalysts that can be used in conjunction with EMOFs. The review suggest that monometallic organic frameworks-based burning rate catalysts have relatively simple catalytic effects, and adding metal salts can improve their catalytic effect. Bimetallic multifunctional energetic burning rate catalysts have excellent catalytic performance and the potential for broad application. The investigation of carbon-supported EMOFs burning rate catalysts is still at a preliminary stage, but their preparation and application have become a research focus in the burning rate catalyst field. The application of catalysts that can be compounded with EMOFs should be promoted. Finally, environmental protection, high energy and low sensitivity, nanometerization, multifunctional compounding and solvent-free are proposed as key directions of future research. This study aims to provide a reference for the application of energetic organic burning rate catalysts in solid propellants.